2009
DOI: 10.1159/000265998
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Percutaneous Endoscopic Gastrostomy in Nursing Home Residents – A Nationwide Survey in Germany

Abstract: Background: Despite extensive discussion about percutaneous endoscopic gastrostomy (PEG) in nursing home residents, no prevalence data exist in most countries. Objective: This study aimed to determine the prevalence of PEG in German nursing homes, as well as nursing home characteristics that may influence this prevalence. Additionally, we documented the timing of PEG insertion, whether pre- or post-admission to the nursing home, and the proportion of residents receiving oral nutrition in addition to tube feeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
24
0
4
Order By: Relevance
“…Seit der Einführung der PEG ist die Zahl ihrer Anwendungen ex ponenziell gestiegen, sodass die se Proze dur beispielsweise in Deutschland mehr als 140.000mal/Jahr durchgeführt wird [68,69]. Unter Beachtung der Indikatio nen und Kontraindikationen (.…”
Section: Perkutane Sondenunclassified
“…Seit der Einführung der PEG ist die Zahl ihrer Anwendungen ex ponenziell gestiegen, sodass die se Proze dur beispielsweise in Deutschland mehr als 140.000mal/Jahr durchgeführt wird [68,69]. Unter Beachtung der Indikatio nen und Kontraindikationen (.…”
Section: Perkutane Sondenunclassified
“…One of the main reasons of controversy may be the fact that enteral nutrition may be used incorrectly to facilitate care or save time instead of spending attention and time to oral feeding. Based on a recent nation-wide mailing survey, it was estimated that about 40,000 NH residents in Germany are living with a PEG [8]. Our present knowledge about nutritional and health status of nursing home residents who are tube-fed is poor.…”
Section: Introductionmentioning
confidence: 99%
“…[16,18,2528] The present study demonstrated that PEG was mainly performed in male patients (74.2%–76.3%) and at medical centers (66.6%–68.7%). This indicates that the use of PEG is influenced by sex, the presence of a nearby medical center rather than by objective clinical assessments.…”
Section: Discussionmentioning
confidence: 77%